2008
DOI: 10.1002/humu.20645
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms ofLIG4andXRCC4involved in the NHEJ pathway interact to modify risk of glioma

Abstract: Although the role of environmental risk factors in the etiology of gliomas remains to be elucidated, accumulative epidemiological evidence suggests that genetic factors, such as variants in genes involved in DNA repair, may also play an important role. LIG4 and XRCC4 are known to form a complex and are functionally linked in the repair of double-stranded DNA breaks. To determine whether LIG4 and XRCC4 polymorphisms are associated with susceptibility to glioma and whether there are interactions between LIG4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 46 publications
2
41
1
Order By: Relevance
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…We have listed about 20 epidemiological studies reporting positive associations between DNA repair polymorphisms and cancer risk (Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] ). Only a small proportion of studies were large (five studies were more than 500 pair cases and controls) and population based; however, some consistencies in results are apparent.…”
Section: Pbts Molecular Epidemiologic Studies With Focus On Dna Repairmentioning
confidence: 99%
“…In our previously published studies, we have demonstrated that some representative tSNPs of genes involved in the NHEJ pathway may modulate risk of gliomas. 23,24 Also, these results suggest that the genetic interaction between DNA repair genes may play an important role in the etiology of gliomas.…”
Section: Discussionmentioning
confidence: 80%
“…23,24 Briefly, all subjects, including case and control groups, were unrelated Han Chinese people from Shanghai City and its surrounding regions in east China. Patients newly diagnosed with pathologically confirmed gliomas were recruited into study group between October 2004 and May 2006 at the Department of Neurosurgery of Huashan Hospital of Fudan University, Shanghai, China.…”
Section: Study Populationmentioning
confidence: 99%
“…Breast Cancer Caucasian The polymorphism was significantly associated with a decrease in breast cancer risk (P = 0.04) Liu et al [100] rs3093739 Glioma Asian The polymorphism was significantly associated with glioma risk (P = 0.009) Liu et al [101] rs7325927 Glioblastoma Caucasian The polymorphism was significantly associated with glioblastoma survival (P = 0.008) SNP: Single nucleotide polymorphism.…”
Section: Caucasianmentioning
confidence: 99%